Prioritizing Enabling Factors of IoT Adoption for Sustainability in Supply Chain Management - Sittiporn Pimsakul; Premaratne Samaranayake; Tritos Laosirihongthong (My University, 2021)
Several studies have reported on enabling factors of IoT adoption, emphasizing the importance of key factors for successful IoT adoption. However, only a few studies have investigated enabling factors with consideration of a sustainability perspective and no similar study has focused on manufacturing from an emerging economy perspective. The main purpose is to investigate enabling factors of IoT adoption from a sustainability perspective. This study aims to (i) identify and select key enabling factors from a comprehensive literature review, and (ii) prioritize them using a multiple criteria decision-making approach, validated through industry experts’ opinions. The results showed that system integration and IoT infrastructure are the top enabling factors in increasing the overall success of IoT adoption. Furthermore, enabling factors of IoT adoption are directly connected with organizational resources/technological capabilities that support the resource-based view theory. Supply chain managers can use the findings of this study to guide and prioritize IoT adoption, and develop strategies for going forward with IoT settings, using the relative importance of enabling factors and interdependencies among them from the technological and organizational perspectives. To generalize these findings through benchmarking of enabling factors in manufacturing, a broader range of industries within the manufacturing sector should be considered in future studies.
Keywords: Benchmarking; Digital Transformation in Industry